We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

#1**+2 **

\(y = {-7 \pm \sqrt{7^2-4(1)(-6)} \over 2}\)

Convenient that the first thing from the LaTeX button is the quadratic formula. (Before this, subtract 6 from both sides. It's now y^{2}+7y-6=0)

Evaluate what is under the root.

-4*-6=24

7^{2}=49

49+24=73

We now have \(y= {-7 \pm \sqrt{73} \over 2}\)

Nothing past this can be done. Your answer is **A** .

rarinstraw1195 Apr 27, 2018